Effects of Tai Chi and Qigong intervention on anxiety and stress in diabetic and hypertensive Brazilian patients: a randomized controlled trial - Laís Renata Almeida Cezário Santos; Anderson Taíra; Rosana de Fátima Possobon; Marcelo de Castro Meneghim; Chien-Lin Su; Paola Lavin; Soham Rej; Gláucia Maria Bovi Ambrosano; Karine Laura Cortellazzi (Einstein (São Paulo))
ABSTRACT Objective: This study investigated the effects of Tai Chi/Qigong practice over 13 weeks on anxiety and perceived stress levels in middle-aged or older Brazilian hypertensive and diabetic individuals assisted in a primary healthcare setting. Methods: Ninety-one patients with diabetes mellitus and/or hypertension diagnosed and followed up at a primary care center were randomized to the Tai Chi/Qigong intervention (n = 45) or waitlist (n = 46) group for 13 weeks. Outcome measures were collected at baseline and at 6 and 13 weeks for anxiety (State-Trait Anxiety Inventory [STAI]) and stress (Perceived Stress Scale - PSS14). The primary endpoint of the study was 13 weeks. We used a linear mixed-effects model to analyze the primary and secondary outcomes, considering the treatment group and time as covariates and treating the subject as a random effect. Results: Of the included 91 participants, 53 completed the 6-week assessment, and 42 completed the 13-week assessment. After 13 weeks, the Tai Chi/Qigong Group had lower scores for anxiety (STAI Estimate = -6.421; SD = 2.679; 95% confidence interval (95%CI) = [-11.615,-1.224]; p = 0.018) and stress (PSS14 Estimate = -9.290; SD= 2.262; 95%CI= [-13.678,-4.906]; p<0.001). Conclusion: A 13-week Tai Chi/Qigong intervention was efficacious in lowering anxiety and perceived stress scores in middle-aged and older patients with diabetes mellitus and hypertension and can potentially be used in primary care centers as an adjunct therapy. Trial registration: Brazilian Registry of Clinical Trials (ReBEC), Identifier: U1111-1276-1787.